2003
DOI: 10.1080/00498250310001636877
|View full text |Cite
|
Sign up to set email alerts
|

‘Open access’ generic method for continuous determination of major human CYP450 probe substrates/metabolites and its application in drug metabolism studies

Abstract: 1. An 'open access' generic high-performance liquid chromatography method was developed for different combination sets each containing specific cytochrome P450 probe substrate and the corresponding metabolite. Method development, optimization and validation were carried out with the following combinations: phenacetin + paracetamol + internal standard (IS, celecoxib), bufuralol + hydroxybufuralol + IS, testosterone + 6beta-hydroxytestosterone + IS, chlorzoxazone + 6-hydroxychlorzoxazone + IS, coumarin + 7-hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Rao et al (2003) have reported an HPLC assay for the simultaneous determination of probe substrates as well the metabolites formed due to the activity of some important CYP isozymes (namely CYP1A2, CYP2A6, 2B6, 2C9, 2C19, 2D6, 2E1 and 3A4). The developed method offers several advantages, including the use of conventional instruments, simple and straightforward handling procedures, simplified data analysis and increased sample throughput by provision of a platform for continuous analysis of different combination sets in a single method.…”
Section: Determination Of a Major Metabolite As A Surrogate For The Pmentioning
confidence: 99%
“…Rao et al (2003) have reported an HPLC assay for the simultaneous determination of probe substrates as well the metabolites formed due to the activity of some important CYP isozymes (namely CYP1A2, CYP2A6, 2B6, 2C9, 2C19, 2D6, 2E1 and 3A4). The developed method offers several advantages, including the use of conventional instruments, simple and straightforward handling procedures, simplified data analysis and increased sample throughput by provision of a platform for continuous analysis of different combination sets in a single method.…”
Section: Determination Of a Major Metabolite As A Surrogate For The Pmentioning
confidence: 99%
“…A C 18 Inertsil ® ODS 3V column (4.6 × 250 mm, 5 µm, GL Sciences Inc., Tokyo, Japan) was used for the analysis. The ternary mobile phase system, consisting of reservoir A (0.01 M ammonium acetate buffer, pH 5.0-acetonitrile; 90:10), reservoir B (0.01 M ammonium acetate buffer, pH 5.0-acetonitrile; 5:95) and reservoir C (0.01 M ammonium acetate buffer, pH 5.0-methanol; 10:90), was run as per the gradient program (Rao et al, 2003) with a total flow rate of 1 mL/min through the column to elute the analytes. The eluate was monitored by the PDA detector (scan range 200-400 nm) and data integration was carried out by Millennium 32 software (version 4).…”
Section: Scopementioning
confidence: 99%
“…Plasma was harvested by centrifuging the blood using a Biofuge (Hereaus, Germany) at 7500g for 5 min and concentrations of total TPT (lactone plus hydroxy acid) were determined using a modified bioanalytical method earlier reported by us (Rao et al 2003).…”
Section: Experimental Design and Pharmacokinetic Studiesmentioning
confidence: 99%